FEATURES OF ECOLOGICAL CARTOGRAPHY OF TERRITORY FOR EDUCATIONAL PURPOSES - Datsenko, L.; Nizhynska, Y. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
The article presents information on the basic principles and rules of ecological mapping of the territory. The discrepancy between creating such maps for the initial purposes use is revealed. An ecological map is a mapping model of ecological states of landscape taxa, which in aggregate reflect the current ecological situation on the territory. An ecological map is a set of discrete values of the state of the geosystem, which gradually change from point to point, covering the entire study area.